Ode marítima: do atual ao inaugural a poesia como poiesis e performance - Cembrone, Kátia Pellicci (2011)
This work aims to demonstrate the reason why Ode Marítima is considered the most important poem of the Sensacionism Moviment, created by Fernando Pessoa and Mário de Sá-Carneiro in the early twentieth-century, by establishing a connection between actual and original, modern and primitive, time and no-time dimensions, chronological time and mythical time. In order to do that, some of the theoretical frameworks used were: the studies of the rhythm structure of this ode, by José Augusto Seabra and Nicolás Extremera Tapia; the studies of oral poetry, developed by Paul Zumthor; Fernando Pessoa and Mário de Sá-Carneiro s writings about Sensacionism; Micea Eliade s studies about myth; and the philosophical view of man s way of life transformations according to Friedrich Nietzsche. In the first chapter, we intended to reflect on the transformations poetry has passed through the time in order to, in the next chapter, explain and justify the sensacionist proposal of a modern art that is based on sensation strength, and intends to touch the sensorial body of its receptor. Finally, we proceeded to an analytic reading of the corpus: the Ode Marítima. We concluded that the poem materializes the Sensacionism by proposing us a return to the origins of the poetry. Thus, Álvaro de Campos modern experiment is access to the archaic rituals rhythm: song, voice, dance, body pure sensation, pure poetry. Such an experiment gives us the possibility of a more conscious perception of the complex way of modern life